2018
DOI: 10.1074/jbc.ra118.004255
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function analyses of the bacterial zinc metalloprotease effector protein GtgA uncover key residues required for deactivating NF-κB

Abstract: The closely related type III secretion system zinc metalloprotease effector proteins GtgA, GogA, and PipA are translocated into host cells during Salmonella infection. They then cleave nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) transcription factor subunits, dampening activation of the NF-κB signaling pathway and thereby suppressing host immune responses. We demonstrate here that GtgA, GogA, and PipA cleave a subset of NF-κB subunits, including p65, RelB, and cRel but not NF-κB1 and NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
(86 reference statements)
2
27
0
Order By: Relevance
“…EHEC NleC is a metalloprotease capable of reducing the amount of histone acetyltransferase p300 in the nucleus, thereby attenuating the expression of the pro-inflammatory cytokine IL-8 gene [97] ( Figure 2D). Salmonella enterica serovar Typhimurium also secretes metalloproteases: PipA, GogA, and GtgA [98,99]. These enzymes target the nucleus and degrade subunits of NF-κB p65, RelB, and cRel.…”
Section: Nucleomodulins Acting As Proteasesmentioning
confidence: 99%
“…EHEC NleC is a metalloprotease capable of reducing the amount of histone acetyltransferase p300 in the nucleus, thereby attenuating the expression of the pro-inflammatory cytokine IL-8 gene [97] ( Figure 2D). Salmonella enterica serovar Typhimurium also secretes metalloproteases: PipA, GogA, and GtgA [98,99]. These enzymes target the nucleus and degrade subunits of NF-κB p65, RelB, and cRel.…”
Section: Nucleomodulins Acting As Proteasesmentioning
confidence: 99%
“…Capsules in S. Typhimurium are wrapped around LPS, which also prevents the inflammatory response induced by TLR4 recognition [181]. Even if TLRs successfully identify the PAMPs, Salmonella SPI-2 encoded proteins, i.e., SseL, SpvD, PipA, GogA, GtgA, SpvC, can inhibit the nuclear factor kappa beta (NF-κB), extracellular signal-regulated kinase (Erk), and mitogen-activated protein kinase (MAPK) activation, thus suppressing the transcriptional responses leading to inflammation (Figure 1) [85,106,[184][185][186]. SseL acts as a deubiquitinase and prevents the ubiquitination of IkB-α.…”
Section: Escape Of Innate Immune Systemmentioning
confidence: 99%
“…enterica and NleC from E . coli are T3SS-injected nucleomodulins that reportedly contain short metal-binding motifs for active-site zinc [ 66 , 117 ]. While these metalloproteases were identified to localize to the nuclei of transfected and infected cells, there is little known regarding the mechanisms used for nuclear translocation [ 118 , 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…While these metalloproteases were identified to localize to the nuclei of transfected and infected cells, there is little known regarding the mechanisms used for nuclear translocation [ 118 , 119 ]. Studies have shown that PipA, GtgA, GogA, and NleC redundantly target components involved in the NF-κB signaling pathway [ 117 , 119 , 120 ]. PipA, GogA, and GtgA cleave RelA (p65), RelB, and occasionally cRel nuclear transcription factors, but do not cleave NF-κB1 (p105/p50) or NF-κB2 (p100/p52) [ 117 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation